KINEMATIC ACTIVITIES OF THE DISK BRAKE (Perner's Contacts, 2011)
Purpose in brakes is stop all advance or rotational motion of drive after turningoff engine and effects the brake position components, it comes to fail safe stopping weight. It discharge a function brakes, which they have constant braking moment. Stop the weight is at stall speed. Constructional are these brakes realized in design as the cheek brake or circular alternatively disk brake already at present little exploited band brakes.
Keywords: Disk brake; brake force; braking moment